Ivermectin-Loaded Mesoporous Silica and Polymeric Nanocapsules: Impact on Drug Loading, In Vitro Solubility Enhancement, and Release Performance - Maiara Callegaro Velho; Nadine Lysyk Funk; Monique Deon; Edilson Valmir Benvenutti; Silvio Buchner; Ruth Hinrichs; Diogo André Pilger; Ruy Carlos Ruver Beck (MDPI AG, 2024)
Ivermectin (IVM), a widely used drug for parasitic infections, faces formulation and application challenges due to its poor water solubility and limited bioavailability. Pondering the impact of IVM's high partition coefficient value (log P) on its drug release performance, it is relevant to explore whether IVM nanoencapsulation in organic or inorganic nanoparticles would afford comparable enhanced aqueous solubility. To date, the use of inorganic nanoparticles remains an unexplored approach for delivering IVM. Therefore, here we loaded IVM in mesoporous silica particles (IVM-MCM), as inorganic nanomaterial, and in well-known poly(ε-caprolactone) nanocapsules (IVM-NC). IVM-MCM had a well-organized hexagonal mesoporous structure, reduced surface area, and high drug loading of 10% w/w. IVM-NC had a nanometric mean size (196 nm), high encapsulation efficiency (100%), physicochemical stability as an aqueous dispersion, and drug loading of 0.1% w/w. Despite differing characteristics, both nanoencapsulated forms enhance IVM's aqueous intrinsic solubility compared to a crystalline IVM: after 72 h, IVM-MCM and IVM-NC achieve 72% and 78% releases through a dialysis bag, whereas crystalline IVM dispersion achieves only 40% drug diffusion. These results show distinct controlled release profiles, where IVM-NC provides a deeper sustained controlled release over the whole experiment compared to the inorganic nanomaterial (IVM-MCM). Discussing differences, including drug loading and release kinetics, is crucial for optimizing IVM's therapeutic performance. The study design, combined with administration route plans and safety considerations for humans and animals, may expedite the rational optimization of IVM nanoformulations for swift clinical translation.